The dynamics of informed trading around corporate bankruptcies - Viet Anh, Dang; Dinh Trung, Nguyen; Pham, Thu Phuong; Ralf, Zurbruegg (Elsevier, 2024)
We investigate the dynamics of informed trading both before and after corporate bankruptcy announcements using high frequency data. Our findings reveal that pre-announcement informed selling attenuates subsequent announcement returns, with this effect being weaker for firms receiving extensive pre-announcement media coverage or adverse news sentiment. We also find that post-announcement informed trading can serve as a predictor of subsequent bankruptcy outcomes. Overall, results are consistent with there being material information leakage, warranting policy efforts to better safeguard less informed investors.